2018
DOI: 10.1021/acsomega.8b02762
|View full text |Cite
|
Sign up to set email alerts
|

Organotemplate-Free β Zeolites: From Zeolite Synthesis to Hierarchical Structure Creation

Abstract: Interest in the production of β zeolites in the absence of organic structure-directing agent (OSDA) has continued to grow consistently during the past decade. During this time, numerous strategies have been proposed to manipulate the hierarchy of zeolite pore structures in order to facilitate the transport of bulky reactants and to improve the accessibility of active sites in zeolite catalysts. In this work, we describe an organotemplate-free route to produce hierarchical β zeolites. Using OSDA-free β as the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This is because during the dealumination and partial dissolution of Beta zeolite in the acid treatment, the morphology of catalysts are changed, the surface becomes rougher, some zeolites appears holes after etching, and some zeolites are dissolved into smaller grains and accumulate to form a nanocrystalline-aggregated morphology. And, the accumulation of 20-30 nm nanoparticles produces a large number of intercrystalline mesopores [15,16]. Thus, the hierarchical Co/Beta zeolite catalyst with a nanocrystalline-aggregated structure was formed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because during the dealumination and partial dissolution of Beta zeolite in the acid treatment, the morphology of catalysts are changed, the surface becomes rougher, some zeolites appears holes after etching, and some zeolites are dissolved into smaller grains and accumulate to form a nanocrystalline-aggregated morphology. And, the accumulation of 20-30 nm nanoparticles produces a large number of intercrystalline mesopores [15,16]. Thus, the hierarchical Co/Beta zeolite catalyst with a nanocrystalline-aggregated structure was formed.…”
Section: Resultsmentioning
confidence: 99%
“…During the acid treatment, the framework aluminums of Beta zeolite are partially removed, and the Beta zeolite particles are partially dissolved and become smaller. This process forms large numbers of intercrystalline mesopores and obtains a hierarchical Co/Beta catalyst with nanocrystalline-aggregated morphology [15,17]. By observing the TEM images of the 10CB-MM and 10CB-IM catalyst samples with high magnification (Figure S1), it is found that the cobalt species particles of the 10CB-MM samples prepared via the melting method are smaller and more uniformly dispersed, with a particle size of about 5-10 nm, while that of the 10CB-IM samples prepared via the impregnation method is larger, with a particle size of about 8-20 nm.…”
Section: Resultsmentioning
confidence: 99%
“…[339] The second group of desilication strategies includes template-free alkaline treatments and has been employed by several groups. In general, most research groups employ a 0.2 m NaOH solution as desilication agent, [340][341][342][343][344] while the effect of other synthesis parameters was explored. For instance, Dos Santos et al investigated the influence of temperature and treatment time on the synthesis outcome.…”
Section: Betamentioning
confidence: 99%
“…[12] Top-down approaches are more reproducible and favored for commercial production of hierarchical zeolites. [20] Destructive or top-down methods include a variety of techniques to introduce a secondary level of porosity in as-synthesized zeolites through post-synthesis modification. Post-synthesis treatments are used to modify and improve the zeolite properties that cannot be achieved through direct synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…[ 12 ] Top‐down approaches are more reproducible and favored for commercial production of hierarchical zeolites. [ 20 ]…”
Section: Introductionmentioning
confidence: 99%